Living the information society in Asia - Alampay, Erwin A.; Institute of Southeast Asian Studies; International Development Research Centre (Canada).; Living the information society (2007 Manila). (Singapore Institute for Southeast Asian Studies, 2009)
"Undeniably, Asian societies are in a period of transition, when people are learning to live with new information and communication technologies (ICTs) -- whether in commerce, government or development work. Living the Information Society in Asia describes the interaction of people and new ICTs as the technologies seep into everyday life, such as how mobile phones forge relationships among families separated by migration, how camera phones threaten personal space, how cultural identities are strengthened in call centres, and how religion is incorporated into the new communication technologies people use. Living the Information Society in Asia looks at the phenomenon as it unfolds and raises the implications for policy and future research."--Back cover.
Foreword / by Laurent Elder -- Preface -- List of abbreviations -- Contributors -- Introduction : perspectives of ICT research in Asia / by Erwin Alampay -- 1. What would Durkheim have thought? Living in (and with) the information society / by Rich Ling -- 2. What is a mobile phone relationship? / by Daniel Miller -- 3. Technologies of transformation : the end of the social or the birth of the cyber network? / by Raul Pertierra -- 4. Becoming mobile in contemporary urban China : how increasing ICT usage is reformulating the spatial dimension of sociability / by Jean-Francois Doulet and Shang Dan -- 5. Mobile religiosity in Indonesia : mobilized Islam, Islamized mobility and the potential of Islamic techno nationalism / by Bart A. Barendregt -- 6. Moral panic and mobile phones : the cultural politics of new media modernity in India / by Gopalan Ravindran -- Stories from e-Bario / by John Tarawe and Roger W. Harris -- Life and death in the Chinese informational city : the challenges of working-class ICTs and the information have-less / by Jack Linchuan Qiu -- Institutional responses to GIS adoption for RPTA in local governments / by Jocelyn C. Cuaresma -- Customer acquisition among small and informal businesses in urban India : comparing face-to-face and mediated channels / by Jonathan Donner -- The view from the other side : the impact of business process outsourcing on the well-being and identity of Filipino call centre workers / by Ma. Regina M. Hechanova -- Empowering Thai homeworkers through ICTs / by Kamolrat Intaratat and Piyachat Lomchavakarn -- Index.
Keywords: Information society -- Asia; Information technology -- Social aspects; Internet -- Social aspects